Aporte de los microcréditos a los comerciantes del Centro Comercial de la Cuidad de Yantzaza - Sarango Alejo, Yesli Yessenia (2023)
Microcredits are a financing system that seeks to contribute to the individual positively. It has become an essential tool at the national and international scale because it has proven to be one of the most important mechanisms for overcoming the economic limitations of micro entrepreneurs. The research was developed to analyze the contribution of microcredits to the traders of the Mall of the city of Yantzaza and its influence on the socioeconomic level, for which a mixed approach was used with a non-experimental design of longitudinal cut, with descriptive scope allowing to analyze the characteristics and fundamental features of microcredits through a survey conducted to 145 merchants, and the application of interviews to three credit managers of the different financial institutions of the locality. The results show that the savings and credit cooperatives are the most influential in the placement of loans in the locality. On the other hand, it was evidenced that 117 merchants have had access to microcredit, and most of them have acquired a microcredit of simple accumulation. The leading destination was the acquisition of products, and their economic contribution was evidenced through the increase in their income, which encouraged savings and generated sources of employment. In addition, it reflected its social contribution to education in the home through purchasing household appliances, as well as stabilizing an emotionally acceptable life for the merchant. In conclusion, microcredit has become a financing alternative for merchants, showing that it fulfills one of the objectives for which it was created, that of helping the micro entrepreneur through financing to generate higher income and maintain a better quality of life.